Bacteremic meningitis caused by Parvimonas micra in an immunocompetent host. (August 2015) - Ko, Jae-Hoon; Baek, Jin Yang; Kang, Cheol-In; Lee, Woo Joo; Lee, Ji Yong; Cho, Sun Young; Ha, Young Eun; Kim, So Hyun; Chung, Doo Ryeon; Peck, Kyong Ran; Lee, Nam Yong; Song, Jae-Hoon
Abstract: A 61-year-old man with chronic hepatitis B and dyslipidemia visited the emergency department with a fever and severe headache. He was diagnosed with bacterial meningitis after a lumbar puncture, and blood culture revealed Parvimonas micra bacteremia. Although he had a history of extraction of a molar two weeks before symptom onset, there was no evidence of abscess formation on physical examination or imaging studies. He was successfully treated with oral metronidazole for 12 days after 9 days of treatment with IV ceftriaxone and vancomcycin. This is the first report of primary bacterial meningitis caused by this organism, which indicates that this organism is capable of being a bacterial meningitis pathogen. Highlights: We report the first case of primary bacterial meningitis by Parvimonas micra. The present case suggests that this organism can cause bacterial meningitis. We treated the patient with oral metronidazole after IV ceftriaxone and vancomycin.